Food, philosophy and love - Ristic, Nevenka (Rhodes University, Faculty of Humanities, Department of Philosophy, 2006)
This thesis is a metaphilosophical investigation into how food can be handled philosophically. The first chapter considers the question of whether food can be the subject matter of philosophy, and concludes that there are three possible ways: Foodist Philosophy, Philosophy of Food, and Philosophy and Food. This thesis focuses on the category Foodist Philosophy. The second chapter develops an account of foodist philosophy: it is a style of philosophy that assumes that our food and eating practices are fundamental aspects of the human condition. The third chapter analyses Plato's concept of love in the Symposium and these conclusions are objected to in a foodist critique in the fourth chapter.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Plato -- Symposium; Food -- Philosophy; Eating (Philosophy); Love -- Philosophy